Modeling physical hypermedia applications - Gordillo, Silvia Ethel (^p Datos electrónicos (1 archivo : 91 KB))
In this paper we present a modeling approach for building physical hypermedia (PH) applications, i.e. those applications in which real and digital objects are navigated using the hypertext paradigm. We first survey the state of the art in this kind of ubiquitous applications. We stress the importance of modeling and design activities and present our design approach, an extension of the well-known Object-Oriented Hypermedia Design Method (OOHDM); we finally discuss some further work we are pursuing in this area.